The Poetics Of Animalistic Characters In Michael Morpurgo’s Works: Theoretical Foundations And Literary Analysis - Yuldosheva Zulfizar Sobir kizi (International Journal Of Literature And Languages, 2025)
This study explores the role and poetic function of animalistic characters in the works of Michael Morpurgo. The research examines the theoretical foundations of anthropomorphism and analyzes how animals are portrayed not just as secondary elements, but as central figures with emotional depth, narrative agency, and symbolic significance. By investigating Morpurgo’s narrative style and thematic focus, this paper reveals how animalistic characters contribute to the moral and philosophical layers of his literature.